Passive solar design for energy efficiency in buildings in composite climate. (August 2019) - Charde, M; Gupta, R; Vemuri, A; Kheterpal, A; Bhati, S
Abstract: Renewable energy sources offer an unlimited supply of energy. Solar energy can be utilized to supplement energy needs of a building either passively or actively. It is feasible to reduce consumption of energy usage for heating, cooling and lighting requirements of a building by adopting a climate sensitive approach for design of building elements like static sunshade, wall and roof. To study the effect of passive building elements in composite climate zone, four rooms were designed with a different combination of type of static sunshade, wall and roof. The static sunshade and brick cavity wall with brick projections were designed using sunpath diagram and shadow angles. Air cavity was introduced in the reinforced cement concrete (RCC) roof by laying hollow stoneware pipes. This paper presents theoretical and simulation studies to compare thermal performance of the four rooms. Theoretically, the four rooms were compared by steady state method based on total heat load in every month and on representative days in different seasons throughout the year. The extreme and most frequently occurring temperature values (mode) in every season were identified by obtaining the frequency distribution of the outdoor air temperature with the software SPSS Statistics (IBM Corp. 2012). Results showed that room with designed passive elements gained minimum heat in summer and moderate summer, while it lost minimum heat in winter and moderate winter. This shows the effectiveness of the designed passive elements in insulating the room interiors from the extreme climatic conditions. The rooms were also simulated using software Autodesk Ecotect Analysis 2011 and their performance was compared on a typical day in each month. Results showed that this software can be helpful for preliminary design to get an idea about the room performance that can help to create thermally comfortable indoor environment for the well being of occupants.